2016
DOI: 10.1007/s00415-016-8368-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and structural brain changes in patients with clinically isolated syndrome at high risk for multiple sclerosis

Abstract: Patients with clinically isolated syndrome (CIS), unlike those with multiple sclerosis (MS), have a selective cognitive impairment which is not consistently related to structural brain changes. Our objective was to characterize a profile of cognitive impairment and its association with structural brain changes in patients with CIS who are at high risk of developing MS. Patients with CIS at high risk for MS on interferon-beta (n = 51) and age-, gender-, and education-matched controls (n = 44) underwent comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
27
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 56 publications
9
27
0
4
Order By: Relevance
“…Four of these studies also examined the relationships between global or regional brain atrophy and cognitive measures but found no associations. 2,[24][25][26] Other studies did not find associations between MRI and cognitive measures presumably due to the small sample size and heterogeneity of studied cohorts. 17,[19][20][21] This study has several limitations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Four of these studies also examined the relationships between global or regional brain atrophy and cognitive measures but found no associations. 2,[24][25][26] Other studies did not find associations between MRI and cognitive measures presumably due to the small sample size and heterogeneity of studied cohorts. 17,[19][20][21] This study has several limitations.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in five cross‐sectional18, 23, 24, 25, 26 and two longitudinal studies,2, 38 which included between 43 and 81 patients in very early stages of MS, no significant associations between MRI lesion burden and cognitive measures were reported. Four of these studies also examined the relationships between global or regional brain atrophy and cognitive measures but found no associations 2, 24, 25, 26. Other studies did not find associations between MRI and cognitive measures presumably due to the small sample size and heterogeneity of studied cohorts 17, 19, 20, 21…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Several early studies showed an inverse association between cognitive ability and lesion volume or number on conventional MRI. [18][19][20] In addition, the magnitude of the association was highly variable among studies. [18][19][20] In addition, the magnitude of the association was highly variable among studies.…”
Section: Introductionmentioning
confidence: 99%